Monetary Independence in Emerging Markets : Does the Exchange Rate Regime Make a Difference? - Philippon, Thomas (IMF Working Papers; Working Paper ;, 2001)
This paper compares the impact of shocks to U.S. interest rates and emerging market bond spreads on domestic interest rates and exchange rates across several emerging market economies with different exchange rate regimes. Consistent with conventional priors, the results indicate that interest rates in Hong Kong react much more to U.S. interest rate shocks and shocks to international risk premia than interest rates in Singapore. The results are less clearcut in the comparison of Argentina and Mexico: While interest rates (and the exchange rate) in Mexico seem to react less to U.S. interest rate shocks, they react about the same to bond spread shocks, in addition to a significant impact on the exchange rate.